Comparative evaluation of artificial rupture of membranes and spontaneous rupture of membranes on course of labour and feto-maternal outcomes - Chauhan, Anjali; Sarkar, bani; Tanwar, Kritika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Present study was undertaken to do a comparative evaluation of artificial rupture of membrane (ARM) and spontaneous rupture of membrane (SRM) on the course of labour and feto-maternal outcome. Methods: It was prospective interventional randomized comparative study including 120 primigravidae (60 in ARM and SRM group each) with cervical dilatation ≥3 cm and intact membranes. Amniotomy was performed in ARM group after enrolment while no intervention in SRM group. Outcomes noted were duration of labor, mode of delivery, APGAR score, NICU stay. Results: Significant reduction seen in duration of labour in ARM group (p=0.0001). Mean duration of labor was 5.24 hours in ARM group while 6.94 hours in SRM group. No significant difference noted in mode of delivery (p=0.082). No significant adverse feto-maternal outcomes were seen with amniotomy. APGAR score and NICU admission had no significant difference among the two groups. Conclusions: ARM can be opted as an intervention with shorter duration of labour without adversely affecting the feto-maternal outcomes. It is safe, reliable and cost effective modality when employed in primigravida and may be considered as a low-cost accessible intervention to reduce prolonged labour and its associated complications.